Quaternionic coupling - Marão, José Antonio Pires; Borges Neto, Manoel Ferreira [UNESP] (Academic Publications, 2014)
Physics is in its development a major challenge to relate fields, this paper presents a proposal to relate classical fields of physics, ie the electric field, magnetic field and gravitational equations by time-dependent. The proposal begins with the work that determines the Cauchy-Riemann conditions for quaternions [1], and the determination of Laplace’s equation in four dimensions[3], it was possible to determine mathematical components important to make the couplings of classical fields discussed above.
Keywords: quaternions; Laplace’s equations; geoemtrical coupling fields